Non‐Surgical Endodontic Treatment of Internal Root Resorption in a Turner's Tooth: A Case Report - Mostafa Ghandi; Soheila Jadidi; Melika Shahriari (Clinical Case Reports, 2025)
ABSTRACT In this case report, we presented the endodontic management of the internal inflammatory root resorption of a Turner's tooth, resulting in root perforations. Despite its significant challenges, proper endodontic treatment in such cases can cause positive prognosis and successful outcome.